2009
DOI: 10.1002/ajp.20649
|View full text |Cite
|
Sign up to set email alerts
|

Assessing chimpanzee personality and subjective well‐being in Japan

Abstract: We tested whether the cultural background of raters influenced ratings of chimpanzee personality. Our study involved comparing personality and subjective well-being ratings of 146 chimpanzees in Japan that were housed in zoos, research institutes, and a retirement sanctuary to ratings of chimpanzees in US and Australian zoos. Personality ratings were made on a translated and expanded version of a questionnaire used to rate chimpanzees in the US and Australia. Subjective well-being ratings were made on a transl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

26
309
4
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 140 publications
(340 citation statements)
references
References 31 publications
26
309
4
1
Order By: Relevance
“…Ratings on this questionnaire are consistent across raters and define a single dimension (30,31,33). In addition, like human subjective well-being questionnaires (6,26,34,35), scores on the present questionnaire are stable over time (31), associated with analogous personality traits (30,31,33), and both heritable and genetically correlated with personality (36,37). Finally, a study in orangutans (27) indicated that, like human well-being (26), higher scores on this wellbeing scale were associated with a longer lifespan.…”
Section: Methodssupporting
confidence: 52%
See 2 more Smart Citations
“…Ratings on this questionnaire are consistent across raters and define a single dimension (30,31,33). In addition, like human subjective well-being questionnaires (6,26,34,35), scores on the present questionnaire are stable over time (31), associated with analogous personality traits (30,31,33), and both heritable and genetically correlated with personality (36,37). Finally, a study in orangutans (27) indicated that, like human well-being (26), higher scores on this wellbeing scale were associated with a longer lifespan.…”
Section: Methodssupporting
confidence: 52%
“…We used three existing samples of great apes (22,27,30), each of which included individuals ranging from infancy to old adulthood. The study was not an experiment and there was no intervention.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…[1] (Weiss et al, 2009), which, together with its predecessors (King & Figueredo, 1997;Weiss et al, 2006), and offshoots (Konečná et al, 2008(Konečná et al, , 2012Iwanicki & Lehman, 2015), has been used to assess personality in several nonhuman primate species (Weiss, 2017). A further 12 items were taken from a questionnaire used to study Hanuman langurs (Konečná et al, 2008) and Barbary macaque personality (Konečná et al, 2012).…”
Section: Questionnairementioning
confidence: 99%
“…Research on nonhuman primate personality bucks this trend (e.g., Koski, 2011a;Massen et al, 2013;Neumann et al, 2013;Konečná et al, 2008Konečná et al, , 2012Morton et al, 2013;Garai et al, 2016;Weiss et al, 2006Weiss et al, , 2007Weiss et al, , 2009Weiss et al, , 2011Weiss et al, , 2012aWeiss et al, ,b, 2015Eckardt et al, 2015;Neumann et al, 2013;Adams et al, 2015;Uher & Visalberghi, 2016).…”
Section: Introductionmentioning
confidence: 99%